Implementasi Kebijakan Pelayanan Administrasi Terpadu Kecamatan (PATEN) di Kantor Kecamatan Katapang Kabupaten Bandung - Permana, Hendra (Jurnal Indonesia Sosial Sains, 2022)
The problem studied is the implementation of the policy of the District Integrated Administrative Service (PATEN) at the Katapang District Office, Bandung Regency in the service of making Identity Cards and Family Cards that have not been running optimally. The purpose of the research is to determine the implementation of the policy by using a qualitative approach through descriptive analysis that describes the situation according to the facts that occurred in the research process without manipulation. Analyzed based on four factors that influence the success or failure of implementation, namely communication, resources, disposition, and bureaucratic structure. Informants as data sources include three elements including structural ranks of officials at the Katapang District Office, functional staff serving as operators, representatives from village level government and the general public. The results of the study indicate that the implementation of the District Integrated Administrative Service (PATEN) policy at the Katapang District Office, Bandung Regency in the service of making Identity Cards and Family Cards in general has achieved quite good results. Communication based on aspects or distribution of information through policy socialization has been carried out in accordance with the provisions but has not achieved optimal results, the clarity is quite clear through appeals, announcements through letters and information boards and Whatsapp Group, and consistency covers the entire service process. Resources include aspects of competent human resources at work because they were prepared in advance, financial resources are adequate, facility resources are adequate even though there are some shortcomings and damages, and authority resources are already available based on regional regulations and Regent regulations. Disposition based on the aspect of bureaucratic appointments is in accordance with the needs and incentives in accordance with policy provisions. The bureaucratic structure based on the SOP aspect is already available through the District Head's decision letter and is linked to the Service SOP and the fragmentation is well established.